Sequential Activation of Lateral Hypothalamic Neuronal Populations during Feeding and Their Assembly by Gamma Oscillations - Altafi, Mahsa; Chen, Changwan; Korotkova, Tatiana; Ponomarenko, Alexey (Journal of Neuroscience, 2024)
Neural circuits supporting innate behaviors, such as feeding, exploration, and social interaction, intermingle in the lateral hypothalamus (LH). Although previous studies have shown that individual LH neurons change their firing relative to the baseline during one or more behaviors, the firing rate dynamics of LH populations within behavioral episodes and the coordination of behavior-related LH populations remain largely unknown. Here, using unsupervised graph-based clustering of LH neurons firing rate dynamics in freely behaving male mice, we identified distinct populations of cells whose activity corresponds to feeding, specific times during feeding bouts, or other innate behaviors-social interaction and novel object exploration. Feeding-related cells fired together with a higher probability during slow and fast gamma oscillations (30-60 and 60-90 Hz) than during nonrhythmic epochs. In contrast, the cofiring of neurons signaling other behaviors than feeding was overall similar between slow gamma and nonrhythmic epochs but increased during fast gamma oscillations. These results reveal a neural organization of ethological hierarchies in the LH and point to behavior-specific motivational systems, the dysfunction of which may contribute to mental disorders.
CRIS-Team Scopus Importer:2024-11-08
Keywords: cell assemblies; electrophysiological recordings; feeding; graph-based clustering; innate behaviors; machine learning